2008
DOI: 10.17221/353-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of soya in pig diets with white lupine cv. Butan

Abstract: ABSTRACT:The purpose of the present study was to evaluate the effect of soya replacement (50 or 100%) with whole (WL) or dehulled seeds (DL) of white lupine cv. Butan in the diets for market pigs. The experiment was performed on 50 pigs in equal numbers of barrows and gilts with the initial mean body weight (BW) of 18.3 ± 2.1 kg, fed isonitrogenous and isoenergetic diets for 100 days. In the experimental starter pigs (18 to 35 kg BW), the mean daily body weight gain (BWG) was 0.61 to 0.64 kg and was insignific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…The highest level of amino acids within the crude protein (AA -97.7 g/16 g N) was in white lupine characterised by a higher essential amino acid index (EAAI) (about 85%) as well as chemical score (CS) (about 60.2%) of restrictive amino acids, and the highest protein efficiency ratio (Sujak et al 2006). Zralý et al (2007Zralý et al ( , 2008 and Písaříková et al (2008) found the following levels in the seeds of cultivated lupines: crude protein from 336.9 to 435.7, lysine from 16.4 to 22.6, methionine 401 et al (2000) from 2.6 to 5.0 and threonine from 11.6 to 15.8 g/kg DM. Dehulling resulted in the increase of protein and amino acid levels by approximately 13%.…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest level of amino acids within the crude protein (AA -97.7 g/16 g N) was in white lupine characterised by a higher essential amino acid index (EAAI) (about 85%) as well as chemical score (CS) (about 60.2%) of restrictive amino acids, and the highest protein efficiency ratio (Sujak et al 2006). Zralý et al (2007Zralý et al ( , 2008 and Písaříková et al (2008) found the following levels in the seeds of cultivated lupines: crude protein from 336.9 to 435.7, lysine from 16.4 to 22.6, methionine 401 et al (2000) from 2.6 to 5.0 and threonine from 11.6 to 15.8 g/kg DM. Dehulling resulted in the increase of protein and amino acid levels by approximately 13%.…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
“…In lupine species cultivated in Europe, the content of crude fibre ranged from 94.4 to 142.0 and acid detergent fibre (ADF) from 124.2 to 192.2 g/kg and was higher compared to soybean according to Straková et al (2006). Písaříková et al (2008) found in the seeds of cultivated lupine species markedly lower level of crude fibre (by 75%) and its components -neutral detergent fibre (NDF -by 70%), acid detergent fibre (ADF -by 69%), and acid detergent lignin (ADL -by 99%) due to dehulling.…”
Section: Fibrementioning
confidence: 99%
“…As suggested in the introduction, the replacement of SBM with lupin meal in the diets of various monogastric animals, including rabbits, turkeys, chickens, and pigs, does not necessarily reduce weight gain (Wu et al 2004;Zraly et al 2008;Volek and Marounek 2009;Zdunczyk et al 2016). However, there have been some reports of weight loss with this replacement (Olkowski et al 2005;Smulikowska et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these requirements, low-alkaloid varieties of sweet lupin (Lupinus albus, Lupinus angustifolius, Lupinus luteus) are considered promising for use in animal feed. Its advantage is that lupin can be used to completely replace soybean meal (Zraly et al 2008;Hernandez and Roman 2016). The use of lupin as an alternative source of vegetable protein for the production of animal feed is increasing rapidly.…”
Section: Doi: 1017221/42/2017-cjasmentioning
confidence: 99%
See 1 more Smart Citation